In the verge of coronavirus pandemic, we are providing FREE access to our entire Online Curriculum to ensure Learning Doesn't STOP!

Ex.9.5 Q1 Algebraic Expressions and Identities Solution - NCERT Maths Class 8

Go back to  'Ex.9.5'

Question

Use a suitable identity to get each of the following products.

(i) \(\begin{align} \;\;\left( x+3 \right)\left( x+3 \right) \end{align}\)

(ii) \(\begin{align}  \;\;\left( 2y+5 \right)\left( 2y+5 \right) \end{align}\)

(iii) \(\begin{align} \;\;\left( 2a-7 \right)\left( 2a-7 \right) \end{align}\)

(iv) \(\begin{align}  \;\;\left( 3a-\frac{1}{2} \right)\left( 3a-\frac{1}{2} \right) \end{align}\)

(v)  \(\begin{align}  \;\;\left( 1.1\text{m }-0.4 \right)\left( 1.1\text{ m}+0.4 \right) \end{align}\)

(vi) \(\begin{align} \;\;\left( {{a}^{2}}+{{b}^{2}} \right)\left( -{{a}^{2}}+{{b}^{2}} \right) \end{align}\)

(vii) \(\begin{align}  \;\;\left( 6x-7 \right)\left( 6x+7 \right) \end{align}\)

(viii) \(\begin{align}  \;\;\left( -a+c \right)\left( -a+c \right)~ \end{align}\)

(ix) \(\begin{align} \;\;\text{}\left( \frac{x}{2}+\frac{3y}{4} \right)\left( \frac{x}{2}+\frac{3y}{4} \right) \end{align}\)

(x) \(\begin{align}  \;\;\left( 7a-9b \right)\left( 7a-9b \right) \end{align}\)

 Video Solution
Algebraic Expressions & Identities
Ex 9.5 | Question 1

Text Solution

What is known?

Expressions

What is unknown?

Simplification

Reasoning:

i) By using the distributive law, we can carry out the multiplication term by term.

ii) In multiplication of polynomials with polynomials, we should always look for like terms, if any, and combine them.

Steps:

The products will be as follows.

(i)  \(\begin{align}\left( x+3 \right)\left( x+3 \right)\end{align}\)

\[\begin{align}&= {\left( {x + 3} \right)^2}\\& = {{\left( x \right)}^2} + 2\left( x \right)\left( 3 \right) + {{\left( 3 \right)}^2} \\& \quad \begin{bmatrix} \left( a + b \right)^2 = {a^2} + 2ab + {b^2} \end{bmatrix}\\& = {x^2} + 6x + 9\end{align}\]

(ii) \(\begin{align}\left( 2y+5 \right)\left( 2y+5 \right)\end{align} \)

\[\begin{align}&= {\left( {2y + 5} \right)^2}\\ &= {{\left( {2y} \right)}^2} + 2\left( {2y} \right)\left( 5 \right) + {{\left( 5 \right)}^2} \\& \quad \begin{bmatrix} \left( {a + b} \right)^2= {a^2}  + 2ab + {b^2} \end{bmatrix}\\&= 4{y^2} + 20y + 25\end{align}\]

(iii) \(\begin{align} \left( {2a - 7} \right)\left( {2a - 7} \right)\end{align} \)

\[\begin{align}&= {\left( {2a - 7} \right)^2}\\&= \left( {2a} \right)^2 - 2\left( {2a} \right)\left( 7 \right)  + \left( 7 \right)^2  \\ & \quad \begin{bmatrix} \left( {a - b} \right)^2 = {a^2}  - 2ab + {b^2} \end{bmatrix} \\& = 4{a^2} - 28a + 49\end{align}\]

(iv)  \(\begin{align} \left( {3a - \frac{1}{2}} \right)\left( {3a - \frac{1}{2}} \right)\end{align} \)

\[\begin{align}& = {\left( {3a - \frac{1}{2}} \right)^2}\\& = {\left( {3a} \right)^2} - \not{\!2}\left( {3a} \right)\left( {\frac{1}{\not\!2}} \right) \! \!+\! \!{\left( {\frac{1}{2}} \right)^2} \\ & \quad [\left( {a - b} \right)^2 = {a^2}  - 2ab + {b^2} ] \\& = 9{a^2} - 3a + \frac{1}{4}\end{align}\]

(v)    \(\begin{align} ( {1.1{\rm{m }} - 0.4} ) ( {1.1{\rm{ m }} + 0.4} )\end{align} \)

\[\begin{align}&= {\left( {1.1\,\,{\rm{m}}} \right)^2} - {\left( {0.4} \right)^2}\\ & \quad [ \left( {a + b} \right)\left( {a - b} \right)  = {a^2} - {b^2}] \\&= 1.21\,\,{{\rm{m}}^2} - 0.16\end{align}\]

(vi) \(\begin{align} \left( {{a}^{2}}+{{b}^{2}} \right)\left( -{{a}^{2}}+{{b}^{2}} \right)\end{align} \)

\[\begin{align}&= \left( {{b^2} + {a^2}} \right)\left( {{b^2} - {a^2}} \right)\\&= {\left( {{b^2}} \right)^2} - {\left( {{a^2}} \right)^2} \\ & \quad[ \left( {a + b} \right)\left( {a - b} \right) = {a^2} - {b^2} ] \\&= {b^4} - {a^4}\end{align}\]

(vii) \(\begin{align} \left( {6x - 7} \right)\left( {6x + 7} \right)\end{align} \)

\[\begin{align}&= {\left( {6x} \right)^2} - {\left( 7 \right)^2} \\ & \quad [\left( {a + b} \right)\left( {a - b} \right) = {a^2} - {b^2}]  \\&= 36{x^2} - 49\end{align}\]

(viii)  \(\begin{align} \left( { - a + c} \right)\left( { - a + c} \right)\end{align} \)

\[\begin{align}&= {\left( { - a + c} \right)^2}\\& = {{\left( { - a} \right)}^2} + 2\left( { - a} \right)\left( c \right) + {{\left( c \right)}^2} \\ & \quad [ \left( {a + b} \right)^2 = {a^2} + 2ab + {b^2} ]\\&= {a^2} - 2ac + {c^2}\end{align}\]

(ix) \(\begin{align} \left( \frac{x}{2}+\frac{3y}{4} \right)\left( \frac{x}{2}+\frac{3y}{4} \right)\end{align} \)

\[\begin{align}& = {\left( {\frac{x}{2} + \frac{{3y}}{4}} \right)^2}\\& = 
{\left( {\frac{x}{2}} \right)^2} + {\not \!2}\left( {\frac{x}{{\not\!2}}} \right)\left( {\frac{{3y}}{4}} \right)  + {\left( {\frac{{3y}}{4}} \right)^2} \\ & \quad [\left( {a + b} \right)^2 = {a^2} + 2ab + {b^2} ] \\& = \frac{{{x^2}}}{4} + \frac{{3xy}}{4} + \frac{{9{y^2}}}{{16}}\end{align}\]

(x)  \(\begin{align} ( {7a - 9b} ) ( {7a - 9b} )\end{align} \)

\[\begin{align}&= \left( {7a - 9b} \right)^2 \\& = \left( 7a \right)^2 - 2\left( {7a} \right)\left( {9b} \right) + ( 9b )^2  \\ & \quad [\left( {a - b} \right)^2 = {a^2} - 2ab + {b^2} ] \\& { = 49{a^2} - 126ab + 81{b^2}}\end{align}\]